Development of a Simulation Model for Scaling-up of Fluid Bed Granulation Processes - Varga, Mónika; Balogh, Sándor; Csukás, Béla; Bézy, Zoltán; Virágh, Mária; Nagy, Tibor (Acta Agraria Kaposváriensis, 2007)
There are two extremely different approaches for the modeling and simulation of the fluidized bed granulation in the literature. The first part of the models, starting from the detailed description of the elementary processes, derives a system of partial integro-differential equations (population balance) for the description of the changing particle size distribution and of the other physical properties. Because of the practically unavailable physical parameters the industrial application of these models is very difficult. The second approach, utilizes the empirical relationships, measured in laboratory and pilot equipments of various size. These relationships, combined with heuristic rules are used to support the solution of practical programs. These empirical models are often not invariant to the size of the equipment. Consequently, some general expert rules used to be combined by the intuitive conclusions about the various materials, while some important knowledge (e.g. about the heat capacity of the construction material) cannot be taken into consideration. In this study a practically usable, intermediate solution has been elaborated, based on the so-called „bed-state diagram”. This essential functionality describes the relationship between the motion and the agglomerating ability (stickiness) of the bed. The generic simulation model describes the state elements and the elementary transitions of the processes. The resulted simulation tool describes the heat balance (including also the heat capacity of the construction material), the solvent balance, as well as the elutriation of the solid particles to the filter, and their cyclic or continuous removal. The particle size distribution and other appropriate physical properties are guaranteed by the wellshaped bed-state diagram in implicit. According to the preliminary applications, the simulation program seems to afford practical help for design and scaling-up.
Keywords: fluidized bed granulation; bed-state diagram; generic simulation model; scaling-up